Photographical Analysis of Macro- and Micro-aesthetic Appearance : a Cross-Sectional Study of Iraqi Adults with Class, Normal Occlusion - Mohammed, Dana R. (Anchor Academic Publishing, 2018)
The first sign of facial beauty was displayed in Egyptian civilization art works as they started to understand the divine or golden proportion that was known as a golden ratio which could be defined as the ratio that considered to be the most aesthetically pleasing to the human's eye and the base of countless mysteries over centuries. In the past, the cephalometic analysis represented an important tool in planning an orthodontic treatment, but today, the focus is mainly on the facial soft tissue and the dental assessment by using photographs. Despite most of the orthodontists are focused primarily on the occlusal discrepancies and mal-relations when discussing the needs of orthodontic treatment with the patients, and the patients and parents are focused mainly on the appearance, the orthodontic diagnosis and treatment planning should have a broader extent, include the occlusion, tooth shape and appearance of the face to have both excellent occlusion and excellent aesthetics, although this is quite difficult, but it is the goal that all orthodontists should pursue. This book represents a master thesis in orthodontics from the College of Dentistry-University of Baghdad/Iraq. The uniqueness of this work comes from that it is the first one that analyses the micro-aesthetic appearance to establish normative values for the Iraqi population and find out whether there is a correlation between apparent mesiodistal measurements of maxillary anterior teeth and facial measurements by an indirect method of measurement, using photographs in a sample of Iraqi population.